Endoscopic Evaluation of Transabdominal Sonographically Suggested Gastric Carcinoma - Alim, MA; Ahad, MA; Rashid, MH; Islam, QT; Ekram, ARMS; Razzaqe, MA (TAJ: Journal of Teachers Association, 2009)
Transabdominal ultrasonography (TAS) is a widely used imaging modality for large variety of abdominal complaints. But indeed it has limited values for diagnosis of gastrointestinal diseases. Literatures on the value of transabdominal ultrasonography on diagnosis and preoperative staging of gastric cancer are sparse. So the aim of this study is to assess the accuracy and limitations of ultrasonography for diagnosis and detection of spreading of gastric carcinoma. Fifty eight sonographically diagnosed patients were included in this study. UGI endoscopy was done in all patients. Five patients were excluded from study because of negative biopsy though endoscopy revealed suspicious lesion. The accuracy of conventional transabdominal sonography of fluid filled stomach was evaluated for diagnosis of gastric carcinoma as compared to endoscopy. The age range was between 14-75 years with mean age 43.5 years (SD ±14.2). The maximum numbers of patients (28.3%) were within the age group 40-49 years. The male and female ratio was 1.2:1. Fifty (94.3%) out of 53 patients of sonographically detectable gastric carcinoma actually have true malignancy proven by endoscopic biopsy and 3 (5.6%) were endoscopically normal & no biopsy was taken. Distal gastric carcinoma has been more precisely located than proximal by sonography. Besides this sonography provided an estimate of extragastric spread of tumour (34%) which is not possible by endoscopy. So in conclusion transabdominal sonography is an useful supportive modality for diagnosis and pre-operative assessment of exogastric spread of gastric cancer and indeed a supplementary diagnostic procedure to endoscopy. doi: 10.3329/taj.v20i1.3089 TAJ 2007; 20(1): 48-51